Low-cost housing complex for government employees of Dhaka South City Corporation 14 no outfall, Dhalpur, Jatrabari, Dhaka 1204 - Muna, Maimuna Ahmed (Brac University, 2023)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Architecture, 2022.